Report 14: Online community involvement in COVID-19 research & outbreak response: early insights from a UK perspective - Pristera,P; Papageorgiou,V; Kaur,M; Atchison,C; Redd,R; Bowman,L; Piggin,M; Ward,H (2020)
The Patient Experience Research Centre (PERC) at Imperial College London is developing research to explore and understand people’s views about, experiences of and behavioural responses to the outbreak in the UK and elsewhere. To guide that effort and to help inform COVID-19 research and responses more broadly - for example in mathematical modelling and policy - PERC launched an online community involvement initiative that sought rapid, early insight from members of the public and aimed to establish a network for ongoing community engagement.Priority areas for COVID-19 research Vaccine development was considered the most urgent research priority for many respondents. Social studies exploring the public’s experiences, risk perceptions and behaviours during this outbreak were necessary and important according to 95% of the respondents. Such research could:Improve the way the current outbreak response is planned and implemented;Improve the way information and guidance is provided to and understood by the public;Optimise the support provided to communities and vulnerable groups; andImprove future outbreak preparedness.Other recommended areas of research included:Understanding the role of the media in influencing how people react and respond;Furthering our basic understanding of the virus – how it spreads, who it affects the most and why, and whether people achieve and maintain immunity after being infected;Critiquing the UK’s response to the pandemic against that of other countries; andEnsuring lessons can be learnt from this outbreak to better equip us for future outbreaks, and public health emergencies in general.Key unmet needs amongst communities The main challenges described by respondents were ineffective communication, including access to information and information overload; and conflicting guidance and misinformation. Respondents’ described feelings of concern, confusion and, in some cases, panic as a result of these communication a